Open Text as a Hybrid Genre: A Procedural and Genre-Based Reading of Khalida Khalil’s A Sea Turbulent on My Palm - Karim Abed Ali Naji (JURNAL PENDIDIKAN BAHASA, 2026)
This study examines the concept of the "open text" as a contemporary literary form that deliberately crosses the conventional boundaries separating poetry, narrative, and drama. Drawing on major genre theory discussions from Aristotle to modern theorists such as Todorov, Genette, and Eco, the paper clarifies how genre expectations operate as both creative constraints and interpretive horizons. The applied part provides a qualitative, close-reading analysis of Khalida Khalil’s book A Sea Turbulent on My Palm (2024) as a representative case. The analysis focuses on (1) language and style (poetic condensation, displacement, internal disclosure, and pronoun duality), (2) genre techniques (the integration of poetic imagery, narrative sequencing, and dramatic dialogue/conflict), and (3) distinctive markers of open-text writing (genre overlap, the centrality of language as both means and end, and the reworking of traditional genre features to fit a hybrid structure). The findings indicate that the book achieves cohesion through a controlled balance of genre resources, where poetic language frames narrative movement and dramatic tension without collapsing into any single dominant genre. The paper argues that the open text is not a random mixture of forms but a purposeful compositional strategy that expands interpretive possibilities while retaining formal coherence.